Isolation and Characterization of a Lytic Vibriophage OY1 and Its Biocontrol Effects Against Vibrio spp. - Gao, Lu; Ouyang, Min; Li, Yi; Zhang, Hui; Zheng, Xiang-Feng; Li, Hua-Xiang; Rao, Sheng-Qi; Yang, Zhen-Quan; Gao, Song (Frontiers in Microbiology, 2022)
Vibrio species are important pathogens of marine animals and aquaculture populations and some of them could cause serious infections in humans through consumption of contaminated seafood and aquaculture products. Lytic bacteriophages can potentially alleviate Vibrio contamination in the aquaculture organisms and in the processing of aquatic products, and have gained significant scientific attention in recent years. In the present study, bacteriophages were isolated from sewage of local aquatic products markets and grown using Vibrio mimicus CICC 21613 as host cells. A lytic vibriophage OY1 belonging to the newly proposed family Autographiviridae and the genus Maculvirus was identified by observation under electron microscope and comparative genomic analysis. The phage OY1 showed lytic activity against 20 strains belonging to 6 Vibrio species. The complete phage OY1 genome consists of a single circular double-stranded DNA of 43,479 bp with a total GC content of 49.27% and was predicted to encode 40 open reading frames (ORFs). To evaluate its potential against vibrios, the one-step growth curve, thermal and pH stability, host range and lytic activity of the OY1 phage against Vibrio species were evaluated. The results showed that phage OY1 had a range of thermal and pH tolerance, and exhibited a significant inhibitory effect on the growth of tested Vibrio species. Bacterial growth in the fish muscle extract juice (FMEJ) inoculated with Vibrio mimicus CICC 21613, V. parahaemolyticus CICC 21617, V. alginolyticus VJ14, and the mixed bacterial culture was reduced by 2.65 lg CFU/mL, 2.42 lg CFU/mL, 1.93 lg CFU/mL, and 2.01 lg CFU/mL respectively by incubation with phage OY1 at 25 °C for 36h. Phage OY1 also showed a strong ability to prevent biofilm formation and destroy Vibrio species biofilms. These results indicate that phage OY1 is a potential biocontrol agent against Vibrio species in the aquaculture industry and in food safety control.